Telecommunications Regulation Handbook - Intven, Hank (Washington, DC: World Bank, 2013)
In recognition of the fundamental importance of an appropriate regulatory environment to accelerate connectivity, and access to information services, this handbook provides a practical reference source, on the methods used to regulate the telecommunications sector around the world, emphasizing best practices. The focus is on practices that promote the efficient supply of telecommunications services in a competitive marketplace. It offers a useful compilation of descriptions, and analyses of regulatory practices, and approaches applied in a wide range of countries. The handbook outlines the various factors that motivated the liberalization of telecommunications markets, i.e., increased growth, and fast innovations for better services; the need to expand and upgrade telecommunications networks with new services; growth of the Internet; of mobile and other wireless services; and, of international trade in telecommunications services. These factors compelled regulatory objectives to foster competitive markets to promote efficient supply of telecommunications, and quality at affordable prices. To this end, licensing telecommunications services, interconnection, price regulation, competition policy, and universal service are presented to form the framework for telecommunications regulation.